Lanthanum-Induced Radiopaque Intestinal Precipitates: A Potential Cause of Intestinal Foreign Bodies - Jason Galo; Bianca Madrid; Warren Kupin (Case Reports in Nephrology)
Lanthanum carbonate is a commonly prescribed oral phosphate binder for use in patients with acute or chronic kidney disease. The elemental form of lanthanum is a soft metal, which will appear radiopaque on a standard X-ray radiograph. This case report illustrates the potential for Lanthanum to masquerade as multiple radiopaque intestinal foreign bodies, leading to the extensive mobilization of medical resources and consultations including serial X-ray monitoring, multiple consultants including acute care and colorectal surgery. Given the few published reports describing this finding in the literature, it is essential to consider Lanthanum precipitates in the differential diagnosis of radiopaque intestinal foreign bodies in patients with chronic kidney disease to avoid unnecessary utilization of medical resources for this predominantly benign condition.